N-acetylcysteine supplementation controls total antioxidant capacity, creatine kinase, lactate, and tumor necrotic factor-alpha against oxidative stress induced by graded exercise in sedentary men - Donrawee Leelarungrayub (2018)
Aim of this study was to evaluate the effects of short-term (7 days) N-acetylcysteine (NAC) at 1,200mg daily supplementation on muscle fatigue, maximal oxygen uptake (VO 2 max), total antioxidant capacity (TAC), lactate, creatine kinase (CK), and tumor necrotic factor-alpha (TNF-). Twenty-nine sedentary men (13 controls; 16 in the supplement group) from a randomized control were included. At before and after supplementation, fatigue index (FI) was evaluated in the quadriceps muscle, and performed a graded exercise treadmill test to induce oxidative stress, and as a measure of VO 2 max. Blood samples were taken before exercise and 20 minutes after it at before and after supplementation, to determine TAC, CK, lactate, and TNF- levels. Results showed that FI and VO 2 max increased significantly in the supplement group. After exercise decreased the levels of TAC and increased lactate, CK, and TNF- of both groups at before supplementation. After supplementation, lactate, CK, and TNF- levels significantly increased and TAC decreased after exercise in the control group. Whereas the TAC and lactate levels did not change significantly, but CK and TNF- increased significantly in the supplement group. Therefore, this results showed that NAC improved the muscle fatigue, VO 2 max, maintained TAC, controlled lactate production, but had no influence on CK and TNF-. © 2011 Donrawee Leelarungrayub et al.